KESENJANGAN FISKAL DANA BAGI HASIL MINYAK DAN GAS BUMI ATAS EKSPLOITASI BLOK CEPU - Titik Kurniawati; Wiwik Widayati; Sulistyowati . (Journal of Politic and Government Studies, 2013)
AbstractThis research exemines the fiscal gap of the Revenue-Sharing on oil andgas resources exploitation in Block Cepu which located between two provinces ofCentral Java and East Java. The asessment used in this research is juridicalnormative method where using the law of Undang-Undang Nomor 33 Tahun2004 Tentang Tentang Perimbangan Keuangan Antara Pemerintah Pusat danPemerintah daerah and Peraturan Pemerintah Nomor 55 Tahun 2005 TentangDana Perimbangan as an approach. Regional Autonomy grants an opportunity forLocal Government to flourish each area. Because of this growth, can not beavoided, the resources generated by Local Government have different quantityand quality. The same thing occured in Block Cepu where the oil and gasresources is located between two provinces of Central Java and East java. Thefiscal gap arises when Blora regency, Central Java does not obtain the Revenue-Sharing because of the exploitation is located in Banyu Urip, Bojonegoro, EastJava but Blora has 34,66% of the oil and gas resources.Based on the research results, Blora regency does not abtain theRevenue-Sharing because of clash with the law Undang-Undang Nomor 33 Tahun2004 which states that the beneficiary of Revenue-Sharing is producing areaswhere the oil and gas are exploited and another regency are located in oneprovince.Keywords: Fiscal Gap, Revenue-Sharing